HISTOMORPHOLOGY OF THE PANCREAS IN FIVE MAMMALS - DR SHASHWATI GEETA DEKA, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Pancreatic transplantation is the only reliable therapy that can help a diabetic patient establish euglycemia without exogenous insulin. The potential of animal tissues as a source for organ transplantation has been advocated for the perennial shortage of human donors, posing problem in establishing viable transplantation programmes.